Age Estimation in Living Adults: An Investigation into Pulp to Tooth Area Ratios - Premalatha Bidadi Rajashekaraiah; Mithilesh N Mishra; Vidyadevi Chandavarkar; Sangeetha Ramu; Swetha Pasupuleti; Sheethal Chandra Aralaguppe Chandraprakash (Oral Sphere Journal of Dental and Health Sciences, 2025)
Introduction: In forensic odontology, age determination of living individuals as part of establishing identity is becoming increasingly crucial. Several studies suggest that assessing the morphological features of adult human teeth using orthopantomograms is more dependable than other approaches for estimating age. These studies require that some corrections be made for size variations in the magnification of radiographs and angulations between the X-ray beam and film. To overcome this problem, some researchers suggest using the pulp/tooth area ratio instead of their direct measurement. Methodology: This study describes an orthopantogram-based method for the estimation of age in living individuals from single-rooted premolars. The reliability of this method was cross-checked by taking measurements from the same sectioned teeth. Result: We found that the radiographs were able to predict the age with 70% accuracy, and the tooth sections were able to predict the age with 73% accuracy. As there was a strong correlation of 85% between the two methods, they are similar in predicting the age of an individual. Conclusion: We concluded that the radiographic method using orthopantomograms is a dependable non-invasive method for the estimation of age in living adult individuals.